Nuptiality Between Theological Aesthetics and Trinitarian Ontology (Teología, 2016)
This article aims to place Nuptiality in the hermeneutic circularity between Antropology and Trinity, in order to recover its speculative strenght for Theology, Philosophy and contemporaneous Mystic. John of the Cross, Edith Stein and Christophe Lebreton’s testimonies become the source from which this paper intends to establish a fruitful bond between Theological Aesthetics and Trinitarian Ontology, which leads to skecht out eight distinctive notes that characterize Nuptiality with a new light.
Keywords: Nuptiality; Theological Aesthetics; Trititarian Ontology; Christophe Lebreton; Edith Stein